Pengaruh Model Pembelajaran Think Pair Share (TPS) terhadap Hasil Belajar Ditinjau dari Minat Belajar Matematika Siswa Kelas X SMA - Sukma Lestari; A. Sriyanti; Hafsyah; Suarti Djafar; Jusmawati (Alauddin Journal of Mathematics Education, 2023)
This study aims to determine the influence of the think pair share learning model on learning outcomes in terms of the interest in learning mathematics of grade X students of SMAN 18 Bulukumba. The population in this study is grade X students of SMAN 18 Bulukumba for the 2017/2018 school year which amounted to 137 students. The samples in this study were taken by simple random sampling technique. The sample in class X1 into a control group of 35 people received learning using conventional models. Class X2, which amounted to 35 people, as an experimental group received learning from the TPS learning model. This study uses quasi-experimental experiments with the form of design is nonequivalent control group design and the data analysis techniques used are descriptive statistics and inferential statistics. The results showed that there was an influence of interaction between the think pair share learning model in terms of learning interest in learning outcomes of grade X mathematics SMAN 18 Bulukumba. This is because hypothesis testing of learning outcomes and interest in learning mathematics shows Sig < α (0.000 < 0.05).